Farmers control practices against the invasive red spider mite, Tetranychus evansi Baker & Pritchard in Benin - Azandémè-Hounmalon, G.Y.; Affognon, Hippolyte D.; Komlan, F.A.; Tamo, Manuele; Fiaboe, K.K.M.; Kreiter, S.; Martin, T. (Elsevier, 2015)
n 2008, the invasive tomato red spider mite Tetranychus evansi (Acari: Tetranychidae), a pest of sola- naceous crops, was identi fi ed for the fi rst time as the cause of serious damage on tomato ( Solanum lycopersicum L.; Solanaceae) crops in Benin. Since then, frequent outbreaks have been observed on Solanaceae and other leafy vegetables such as purple amaranth ( Amaranthus cruentus L.; Amaranthaceae) and bitter leaf ( Vernonia amygdalina D.; Asteraceae) in all growing areas in southern Benin. The objective of this study was to evaluate the intensity of damage by this invasive pest and the impact of farmers' control practices on purple amaranth, African eggplant (Solanum macrocarpon L. ; Solanaceae) and tomato crops. A survey was carried out in January 2013 among 150 farmers in the three major growing areas in southern Benin: S